The Enhancement of Catharanthine Content in Catharanthus roseus Callus Culture Treated with Naphtalene Acetic Acid - DINGSE PANDIANGAN; NELSON NAINGGOLAN (Bogor Agricultural University, Indonesia, 2006)
The research aim was to examine the enhancement of catharanthine content in Catharanthus roseus callus culture added with different concentration of Naphtalene Acetic Acid (NAA). NAA treatment produced callus that formed hairy roots. Fresh and dry weight of callus increased as the increasing of NAA concentration. The catharanthine content of C. roseus callus culture was increased by adding NAA as well. The highest catharanthine content was found in 2.5 ppm NAA added callus. Key words: Catharanthus roseus, callus, catharanthine, NAA